2014
DOI: 10.1097/nt.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a New Food Value Analysis Application to Evaluate Trade-offs When Making Food Selections

Abstract: Consumers face a wide variety of options when selecting foods to feed themselves and their households, and they must balance a host of factors, including cost, preparation time, nutrition, taste, cooking skills, shelf life, food waste, and food safety. Each of these factors adds or subtracts value and helps determine the true cost of a food item based on an individual's personal value system. If a single variable, such as cost, is examined, it may provide an incomplete picture of the true value of that food. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…[42], in free range production systems is considerably higher than in conventional battery cage systems [42,43]. The problem is further aggravated by the increase in the consumption of meals consisting of raw egg products [44]. Therefore, egg producers should consider eggshell cleaning and disinfection of table eggs as a priority to produce safe eggs and maintain consumer confidence.…”
Section: Discussionmentioning
confidence: 99%
“…[42], in free range production systems is considerably higher than in conventional battery cage systems [42,43]. The problem is further aggravated by the increase in the consumption of meals consisting of raw egg products [44]. Therefore, egg producers should consider eggshell cleaning and disinfection of table eggs as a priority to produce safe eggs and maintain consumer confidence.…”
Section: Discussionmentioning
confidence: 99%
“…This places a lot of pressure on the control and management of Salmonella during food handling and preparation. The importance of management of this pathogen during food handing has been further increased by the growing desire of consumers for raw food products [ 16 , 17 ]. Humphrey et al [ 56 ] demonstrated using a model kitchen and experimentally contaminated intact eggs that utensils used to mix eggs were sometimes Salmonella positive even after washing.…”
Section: Food Handling and Preparationmentioning
confidence: 99%
“…In recent years, there has been shift driven by consumers for more humane methods of egg production, causing a shift from conventional battery cage housing systems to free-range production [ 15 ]. There has also been a shift in consumer eating habits with increasing demand for raw and unprocessed foods [ 16 , 17 ]. The increasing popularity of unprocessed home-made foods containing raw eggs such as mayonnaise, certain sauces and raw egg based deserts like ice-cream, tiramisu and even milkshakes potentially increases the risk of salmonellosis [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…When selecting food for themselves and their families, consumers deal with a wide variety of options and must balance many factors such as cost, preparation time, nutrition, taste, cooking skills, shelf life and food waste (Kretser et al , 2014). In recent years, due to increased consumer sensitivity regarding food production and consumption, determining factors related to food safety have also become present in food choices (Cagri-Mehmetoglu, 2018).…”
Section: Introductionmentioning
confidence: 99%